Conservative kidney management program components in a resource limited setting: South Africa - Zungu, Christopher Menzi (Adolescent Health Research Institute, 2026)
Background: End Stage Kidney Disease (ESKD) is emerging as one of the most challenging diseases on the rise and unfortunately very expensive to manage. Countries, including South Africa (SA), have a challenge in equitably providing resources to meet the needs of patients with ESKD. In some SA tertiary institutions, more than half of patients who apply for enrolment into Renal Replacement Therapy (RRT) program are not selected due to resource limitation in the dialysis program. Many patients with ESKD are managed in Primary Health Care (PHC) settings with either no access to Palliative Care (PC) and/or prompt referral. There is a need for a standardised program that is well informed by policy to improve the delivery of care for patients with ESKD, especially those who fall under the choice restricted Conservative Kidney Management (CKM) pathway of Kidney Supportive Care (KSC). Aim: This study aimed to determine the perceived standards or components of care in providing CKM services in low resourced countries like SA. Objectives: To describe standards or components of a CKM program; to identify available CKM documents in SA; and to analyse SA CKM documents according to perceived standards or components of a CKM program. Methodology: This was a qualitative study with semi-structured expert interviews, in-depth interviews and document analysis of SA ESKD documents. Participants were selected purposefully and through snowballing. Of the participants, seven (7) were in SA, one (1) in Australia and one (1) in Uganda. Secondary data collections were conducted through desktop analysis of SA ESKD documents. Data were analysed through thematic analysis coded using inductive, and some aspects of deductive analysis guided by the health systems building blocks. The NVivo version 12 software data analysis tool was utilised. A data extraction template was used to extract data from documents that met inclusion criteria for the study. Findings: While dialysis and kidney transplantation are highly technical elements of KSC and generally need the technical leadership of a nephrologist. The comprehensiveness of KSC requires other stakeholders who specialise in preventative and palliative care medicine for its full delivery. A more integrated interdisciplinary response is needed for a successful CKM program. Furthermore, it is not only CKM patients that must move from tertiary facilities to primary care centres, but information, resources and skills must also move and be available in primary care centres for continuity of care. Choice restricted CKM without a proper CKM program leads to patient presenting in acute settings without Advance Care Planning (ACP) leading to an increase in health care cost with repeated extensive workups costing countries more in both direct and indirect costs. Poor organ transplantation policy framework does not only require support with funding, but also relies on a good organ transplant policy framework and increased public awareness on organ donation. Most analysed documents where silent on transplant policy framework involvement, leadership and financing of CKM programs. The confusion in KSC terminology was also noted on analysed documents. It is important that policies and documents in LMICs align themselves with the new core curriculum as led by the ISN to avoid confusion of terms and definitions of KSC and CKM. Conclusion: This study has identified the need for and proposed an essential package of service for CKM in a low resourced setting like SA. This study proposes that such a package should be founded on the health systems building blocks and all components should be integrated, coherent and coordinated. This study will serve as a baseline study for more in-depth studies and possible a CKM program framework. CKM program needs to be funded as per commitment by SA, a co-sponsor of WHA 67.19 resolution which states that all clinicians working in areas with a high burden of patients (such as nephrology) in need of PC need intermediate level training in PC as a matter of urgency.